2021
DOI: 10.1021/acsaem.1c03137
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost and Large-Scale Fabricating Technology for High-Performance Lithium-Ion Battery Composite Separators with Connected Nano-Al2O3 Coating

Abstract: The ever-increasing demand for high power density improves lithium-ion batteries. However, the poor microporous structure and inferior compatibility of separators heighten the lithium-ion migration barrier. Based on the cavitation of β-crystal polypropylene (β-iPP), separators with connected nano-Al2O3 coating are prepared by facile extrusion and biaxial stretching processes of β-iPP and nano-Al2O3. The crystal structure and microporous morphology diagnoses indicate that the moderate nano-Al2O3 content refines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…a) Nyquist plots of symmetrical SS||SS cells and b) EIS results of symmetrical Li||Li cells with PP, PEN, PEN@PDA, and MOFs/NA/MOFs separators; c) Comparison of ionic conductivity of various separators; Comparison of linear sweep voltammetry (LSV) curves of the d) PP, e) PEN, and f) MOFs/NA/MOFs separators;g) Comparison of ionic conductivity and t Li + of the reported separators and separators in this work; [ 9,12,29 ] h) Raman signals of free EC and AWL in electrolytes. i) Raman signals of Li + ‐EC and free EC in electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…a) Nyquist plots of symmetrical SS||SS cells and b) EIS results of symmetrical Li||Li cells with PP, PEN, PEN@PDA, and MOFs/NA/MOFs separators; c) Comparison of ionic conductivity of various separators; Comparison of linear sweep voltammetry (LSV) curves of the d) PP, e) PEN, and f) MOFs/NA/MOFs separators;g) Comparison of ionic conductivity and t Li + of the reported separators and separators in this work; [ 9,12,29 ] h) Raman signals of free EC and AWL in electrolytes. i) Raman signals of Li + ‐EC and free EC in electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…Lower interface impedance generates excellent separator–electrode compatibility and improves ion diffusion through the separator–electrode interface. Also, higher ionic conductivity and Li + transport number accelerate Li + transport within the separator and depress contra‐ion polarization 37,46 . All the above‐mentioned conditions contribute to an optimized discharge capacity of cells packaged with PE‐S‐Al.…”
Section: Resultsmentioning
confidence: 99%
“…PP, Al 2 O 3 , and PE were mixed with masterbatch again to obtain three cast films, namely, PP (pure β-iPP), PP-Al 2 O 3 (95 wt % β-PP + 5 wt % Al 2 O 3 ), and PP–Al 2 O 3 –PE (70 wt % β-PP + 5 wt % Al 2 O 3 + 25 wt % PE). Our previous study , suggested that 5 wt % nano-Al 2 O 3 has the best optimization effect on the microporous structure. Excessive nano-Al 2 O 3 (>5 wt %) agglomerates severely within β-iPP and worsens the pore size dispersion in reverse.…”
Section: Experimental Partmentioning
confidence: 97%
“…Blending hydrophilic nano-Al 2 O 3 into β-iPP cast film imports affluent infirm interfaces between two phases. In the circumstances, the crude fibrils originating from contracted β-lamellae during longitudinal draw can be refined during transverse drawing because of the presence of nano-Al 2 O 3 /β-iPP infirm boundaries in 40,41 suggested that 5 wt % nano-Al 2 O 3 has the best optimization effect on the microporous structure. Excessive nano-Al 2 O 3 (>5 wt %) agglomerates severely within β-iPP and worsens the pore size dispersion in reverse.…”
Section: Introductionmentioning
confidence: 99%